Integrating of Digital Literacy and Figurative Meaning Comprehension: A Cognitivism-Based Semantic Perspective - Saraswati, Saraswati; Anriani, Nurul; Hidayat, Sholeh (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2025)
The digital era has transformed how information is conveyed, shifting messages beyond formal text to encompass online news, social media, digital ads, and metaphor-rich memes filled with cultural symbols and figurative expressions. However, students' skills in grasping these concealed meanings remain underdeveloped, necessitating research that integrates digital literacy with meaning-making theories. This context underscores the need for research that systematically integrates digital literacy with theories of meaning construction. This study seeks to determine how effectively students interpret figurative meanings and to elucidate their underlying thought processes through the lens of cognitive semantics, which views metaphor as a systematic connection between two domains, and Piaget's theory of cognitivism, including assimilation, accommodation, and equilibration in conceptual schema development. This research employs a descriptive qualitative approach, involving 20 students as participants. Data were collected through note-taking from seven DetikNews online articles, figurative meaning comprehension tests, and semi-structured interviews to explore students' reasoning and the rationale behind their thinking. The findings indicate that students are able to map metaphors such as politics as theater, global crises as storms, reshuffles as adjustments, and wayang symbols as leadership representations, and recognize the legal implications of meme dissemination. It was observed that students' figurative understanding is shaped by the activation of conceptual schemas and proficient digital literacy, underscoring the importance of integrating these elements to enhance critical and interpretative thinking when engaging with digital texts. Abstrak Perubahan bentuk komunikasi di era digital membuat pesan tidak lagi dalam teks formal, melainkan melalui media sosial, berita daring, iklan digital, hingga meme yang sarat metafora, simbol budaya, dan ekspresi figuratif. Di sisi lain, kemampuan mahasiswa dalam menafsirkan pesan implisit tersebut masih terbatas dan bersifat literal sehingga menuntut kajian yang mengintegrasikan literasi digital dengan kerangka teoretis pemaknaan. Kondisi ini menunjukkan pentingnya kajian dengan menggabungkan literasi digital dan kerangka teoretis yang menjelaskan proses pemaknaan. Penelitian ini bertujuan menganalisis kemampuan mahasiswa dalam memahami makna figuratif, menjelaskan proses kognitif yang melandasinya melalui perspektif semantik kognitif yang memandang metafora sebagai pemetaan sistematis antara domain sumber dan domain target berbasis kognitivisme Piaget yang meliputi mekanisme asimilasi, akomodasi, dan ekuilibrasi dalam pembentukan skema konseptual. Penelitian menggunakan pendekatan kualitatif deskriptif dengan partisipan 20 mahasiswa. Data dikumpulkan melalui teknik baca–catat pada tujuh berita daring DetikNews, tes pemahaman makna figuratif, dan wawancara semi-terstruktur untuk menggali pengalamn belajar dan proses berpikir mahasiswa. Hasil penelitian menunjukkan mahasiswa mampu memetakan metafora seperti politik sebagai pertunjukan, krisis global sebagai badai, reshuffle sebagai respons adaptif, serta simbol wayang sebagai representasi kepemimpinan, dan memahami bahwa penyebaran meme memiliki konsekuensi hukum. Diperoleh temuan bahwa makna figuratif mahasiswa terbentuk melalui aktivasi skema konseptual dan literasi digital yang baik, sehingga integrasi keduanya penting untuk meningkatkan kemampuan berpikir kritis dan interpretatif dalam membaca teks digital.